Influence of Radial Deformation on Stress of Flexspline and Meshing Characteristic of Harmonic Reducer - Zhang Liyong; Liu Xinmeng; Wang Changlu; Wei Leyu; Qiao Xuetao; Wang Ruifeng (Jixie chuandong, 2017)
The radial deformation is one of the important parameters that affect meshing characteristic and the life of flexspline in harmonic reducer. Based on envelope meshing theory of harmonic drive,the influence of radial deformation on meshing characteristic of harmonic drive is analyzed. The finite element method is used to obtain the stress distribution of the flexspline. The results show that the radial deformation has significant influence on the meshing track,the radial deformation of the flexspline,the tangential deformation,the rotation angle in normal direction,the bending stress and the tangential stress of the flexspline. The result of the flexspline stress distribution from theoretical calculation has good consistent with the result from finite element analysis.This can provide some reference for the choosing of reasonable radial deformation to improve meshing performance and life of flexspline.